Semi-physical mean-value NOx model for diesel engine control. (July 2015) - Quérel, C.; Grondin, O.; Letellier, C.
Abstract: A semi-physical model has been developed to predict nitrogen oxide (NO x ) emissions produced by diesel engines. This model is suitable for online NO x estimation and for model-based engine control. It is derived from a zero-dimensional thermodynamic model which was simplified by only retaining main phenomena contributing to NO x formation. The crank angle evolution of the burned gas temperature, which has a strong impact on NO x formation rate, is described by a semi-empirical model whose key variable is the maximum burned gas temperature. This variable presents a good correlation with the molar fraction of NO x at the end of combustion and can be expressed as a function of the intake burned gas ratio and the start of combustion. The maximum burned gas temperature sub-model is then coupled to an averaged NO x formation kinetic model (based on the Zeldovich mechanism) to form a mean-value model for NO x computation. This latter model was validated using data sets recorded in two diesel engines for steady-state operating conditions as well as for several driving cycles including parametric variations of the engine calibration. Abstract : Highlights: New control-oriented model to predict NO x emissions in diesel engines. Semi-physical mean-value burned gas temperature and average NO x kinetic models. Experimental validation of the virtual NO x sensor in steady-state and transient operations. Computation time compliant for online NO x estimation on series ECU.